Cutaneous manifestations of congenital malignant rhabdoid tumor: Unusual papillomatous plaques and other skin presentations. Issue 4 (23rd April 2020) - Luu, Minnelly; Halbert, Anne; Yan, Albert; Rubin, Adam; McMahon, Patrick; Liang, Marilyn; Vadeboncoeur, Sophie; Frieden, Ilona J.; Maguiness, Sheilagh
Abstract: Background/Objectives: Malignant rhabdoid tumors (MRT) are highly aggressive tumors with a predilection for the kidney, central nervous system, and soft tissues that usually affect young children under three years of age. Primary presentation in the skin is rarely reported, and features of the cutaneous manifestations are not well described. We report six cases of metastatic MRT that first manifested with congenital nodules and masses in the skin. Methods: Retrospective case series. Results: The cutaneous presentation of MRT may be heterogeneous and can present with solitary or multifocal skin lesions. Congenital polypoidal and papillomatous plaques, including those with histologic features of neurovascular hamartoma, appear to be a unique presentation of MRT in the infant. Conclusions: Malignant rhabdoid tumor should be considered in the differential diagnosis of unusual skin tumors in neonates and infants.